Family Employability Development Plan. Evaluation Summary of the Second Year of the Pilot Program (Program Evaluation for 1987-88) - Mavis, Brian ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1988)
The goal of the second year of the Family Employability Development Plan (FEDP) was to increase the number of sites participating in the project implementation. FEDP was developed as part of the Job Training and Partnership Act (JTPA) 8% State Plan. Its major focus was to provide a coordinated service effort for families in Michigan who were dependent on public assistance in an effort to promote the economic independence of the families. Ten new sites implemented the model during the second year. Program providers had little difficulty in recruiting participants. Facilitators identified existing assets and barriers to employment for the family unit. Barriers were characteristic of hard-to-serve families. Each model that was implemented contained these key components: family identification and recruitment, assessment of family and individual attributes, family problem-solving and goal setting, case conferences with other service agencies, meetings with the family to monitor progress, and follow-up. FEDP facilitators engaged in these types of activities: direct contact, advocacy, administration, family intervention, in-home visits, counseling, and family interviews. Outcomes included completion of various levels of education and training programs, increased employment, and greater self-esteem for individuals and families. (Instruments and findings are appended.) (YLB)
Sponsoring Agency: Michigan State Dept. of Education, Lansing. Adult Extended Learning Services.
ERIC Note: For a related document, see CE 052 174.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Adults; Career Education; Demonstration Programs; Economically Disadvantaged; Employment Potential; Family Programs; Federal Aid; Federal Legislation; Job Skills; Program Development; Program Evaluation; Program Implementation; State Programs; Welfare Recipients; Welfare Services; Job Training Partnership Act 1982; Reports, Evaluative